Evidential Adverbs and Polarity: A Study from Spanish - Teresa María Rodríguez Ramalle (Languages, 2023)
This paper addresses the analysis of variations in structures that are projected in discourse. Starting with the relationship between evidential adverbs and the affirmative Spanish adverb sí, I review the occurrence of the conjunction que “that” with evidential adverbs, such as naturalmente “naturally”, ciertamente “certainly”, obviamente “obviously”, and evidentemente “evidently” as a Hispanic phenomenon, as well as its value and development in different varieties of Spanish. Although it appears that Latin American Spanish varieties lack an overt que in certain situations, such as sí que contexts or recomplementation, studies of the construction with evidential adverbs in language varieties different from European Spanish remain limited. I use examples extracted from CREA and CORPES XXI. My main objectives are to review the presence of the construction with evidential adverb + que (“that”) in Spanish by paying particular attention to its distribution in Latin American countries and to study the basic uses of the construction in countries in which it is documented.